THE ROLE OF ISLAMIC KINGDOM CHARACTERS IN NUSANTARA IN MAINTAINING THE INDEPENDENCE OF THE REPUBLIC OF INDONESIA 1945-1950 - Agus mursidi; Dhalia Soetopo; Davi Grace Tiawan (MAN Insan Cendekia Jambi, 2021)
The purpose of writing an article entitled